Potential and partnerships in innovations in EU-funded research projects - Daniel Nepelski; Giuseppe Piroli (Economics and Econometrics Research Institute (EERI), 2016)
We analyse the relationship between the composition of innovation partnerships and the potential of their innovations developed within EU-funded research projects under the Seventh Framework Programme for Research and Technological Development (FP7), the European Union's Research and Innovation funding programme for 2007-2013. Innovation potential is assessed using a formal framework capturing three different dimensions: innovation readiness, management and market potential. Both the analysed innovations and innovators were identified by external experts during periodic Framework Programme reviews. Thus, our population includes participants in the FP7 projects that are considered as key organisations in the project delivering innovations in FP7 projects. We show that the innovative potential of research output of homogenous partnerships, e.g. between two SMEs or two large companies, is likely to be higher, as compared to heterogeneous partnerships, e.g. an SME and a large company. The impact of universities on the potential of innovations is unclear. The total number of key organizations in delivering an innovation has a negative impact on its potential. Neither project funding nor duration affects the potential of innovation. Our results contribute to the discussion on the most appropriate design of R&D consortia of organizations in publically-funded projects.
Keywords: L52; L53; O31; O32; O25; 330; R&D consortia; innovation policy; framework programme; small and mediumsized enterprises